PENINGKATAN KEPEDULIAN CINTA LINGKUNGAN MELALUI PEMBELAJARAN BERBASIS KONSERVASI DI SDN 023 PULAU KIJANG - Melladi, Melladi (Jurusan Ilmu Pendidikan Fakultas Keguruan dan Ilmu Pendidikan Universitas Riau, 2019)
This study aims to create a comfortable, beautiful, and effective learning environment. The study applies the school action research by implementing learning based conservation using daily activity plans and environmental care observation sheets. The subjects of this study are 37 elementary students from Sekolah Dasar Negeri (SDN) 023 Pulau Kijang in the 2017/2018 school year. The research instruments consist of student and teacher observation sheets. The findings indicate that learning based school environmental conservation could improve students’ learning results. The average of students’ learning result in the first learning cycle was 64.86, and it improved in the second learning cycle into 84.94. This means that conservation in the school environment can improve students’ awareness of environmental care in SDN 023 Pulau Kijang